Dampak Dualisme Peraturan Sabun Cuci Tangan - Iin Febrianti Sende; Anita Kembaren; Warmanto Firmansyah; Zein Fadhlurrahman (Eruditio : Indonesia Journal of Food and Drug Safety, 2021)
During the Covid-19 pandemic, people’s need for hand soap has increased which on the other hand is used by business actors to produce and selling more than before. Currently, there is a dualism of hand soap regulations in Indonesia, hand soap can be registered as Household Health Supplies (PKRT) which is supervised by the Ministry of Health, and as Cosmetics which is supervised by Indonesian FDA. The research aims to determine the trend of hand soap distribution and the potential impact of the dualistic condition of hand soap regulations, as a form of early detection to prevent or reduce crime in the cosmetic sector, especially for hand soap products. The research was conducted by collecting registration data and distribution data through direct field research and online mapping in e-commerce. The results showed that hand soap registered as cosmetics is more than as PKRT, and there was an increase in the number of registration data for hand soap as PKRT and Cosmetics during 2020. Based on the results of monitoring distribution in online and offline media, it is known that there are hand soaps registered as Cosmetics, PKRT, PKRT and cosmetics (double distribution permits), and illegal (do not have distribution permits). The dualism of hand soap regulation can confuse supervisory and enforcement officers in handling illegal hand soap, as well as potentially be exploited by criminals who produce and distribute illegal hand soap. This also has an impact on the existence of hand soap that has a double distribution permit (PKRT and Cosmetics) which is considered inefficient and can harm business actors. Indonesian FDA must take strategic steps to resolve the dualism of hand soap regulations, by coordinating with the Ministry of Health and intensifying the supervision of hand soap distribution in the market.